2018
DOI: 10.3892/ol.2018.9602
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity and phytochemical composition of wild Gundelia�tournefortii

Abstract: Artichoke-like wild thistles are often used in Palestinian cuisine. One of the most commercially recognized species of these wild edible thistles is Gundelia tournefortii, a common plant in the Mediterranean region. G. tournefortii, or 'Akoob' in Arabic, remains uncultivated, harvested wild by local populations and considered highly valuable due to its reputed health benefits. The present study aimed to investigate the anticancer effects of G. tournefortii on the human colon carcinoma HCT-116 cell line. Methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 12 publications
1
31
0
2
Order By: Relevance
“…Stigmasterol inhibits angiogenesis through the VEGF signaling network. It reduces the phosphorylation form of FAK, PCL, SRC, and VEGFR2 and inhibits endothelial cell proliferation and migration as well as well capillary network formation through disruption of the TNF–VEGFR2 axis [122].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stigmasterol inhibits angiogenesis through the VEGF signaling network. It reduces the phosphorylation form of FAK, PCL, SRC, and VEGFR2 and inhibits endothelial cell proliferation and migration as well as well capillary network formation through disruption of the TNF–VEGFR2 axis [122].…”
Section: Resultsmentioning
confidence: 99%
“…Stigmasterol was shown to exhibit antiangiogenic activity through inhibiting TNF-α. Recently, it was revealed that Gundelia tournefortii , a rich source of stigmasterol, affects angiogenesis through disruption of the TNF–VEGFR2 axis [122]. Therefore, the compelling data above reveal new insights and suggestions about the use of natural products and their derivatives against different oncogenic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants are natural substances that have health‐promoting properties, such as reducing the incidence of cardiovascular disease (Griffiths et al., 2016; Munir, Chandrasekaran, Gao, & Quon, 2013) and Alzheimer's disease (Hiremathad, 2017; Hiremathad & Piemontese, 2017) as well as anticancer activities (Griffiths et al., 2016; T. T. Zhao et al., 2019). It could be attributed to their redox properties, which include potential mechanisms, such as free‐radical scavenging activity (Abu‐Lafi, Rayan, Kadan, Abu‐Lafi, & Rayan, 2019; Morita, Naito, Niki, & Yoshikawa, 2017), transition metal‐chelating activity (Lu et al., 2010), and 1 O 2 quenching capacity (Terao, Minami, & Bando, 2010). In addition, antioxidants reportedly have a protective effect against food deterioration by ROS and RNS during plasma treatment (Garofulić et al., 2015).…”
Section: The Impacts Of Paw Treatment On Food Qualitymentioning
confidence: 99%
“…Palestine possesses a wide array of biodiversity, despite its limited area [8]. Although exploration for medicinal plants from Palestine for their antioxidant and antimicrobial benefits has improved over the last decade, a huge number of medicinal plants remain to be investigated [9,10]. Certain wild plants have acquired a reputation among Palestinians, since they are an integral component of the culture.…”
Section: Introductionmentioning
confidence: 99%